2011
DOI: 10.1088/0004-637x/741/2/71
|View full text |Cite
|
Sign up to set email alerts
|

THE ELUSIVE60Fe IN THE SOLAR NEBULA

Abstract: No 60 Ni or 61 Ni anomalies have been detected in troilite inclusions from Muonionalusta, a 4565.3 ± 0.1 Ma old IVA iron meteorite, to the level of the analytical precision of 10 ppm. Because Muonionalusta troilite is very old, has a high Fe/Ni ratio, and is free of 61 Ni anomalies, it is the ideal material in which to search for potential excesses of 60 Ni produced by the decay of 60 Fe (t 1/2 = 2.62 Ma). The 60 Ni/ 58 Ni and Fe/Ni ratios (up to 1680) measured here imply an upper limit for the initial 60 Fe/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 66 publications
(79 reference statements)
1
17
1
Order By: Relevance
“…Recent evidence has raised doubts about the initial amount of 60 Fe present in the solar nebula. Moynier et al (2011) presented evidence for an initial ratio of 60 Fe/ 56 Fe less than 3 × 10 −9 , roughly 100 times smaller than previously published ratios (e.g., Mishra et al 2010), while Tang & Dauphas (2012) found an initial ratio of 1 × 10 −8 . The initial level of 60 Fe is particularly significant, as its efficient production requires stellar nucleosynthesis (Tachibana et al 2006) in either a massive star supernova or an AGB star (Huss et al 2009).…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Recent evidence has raised doubts about the initial amount of 60 Fe present in the solar nebula. Moynier et al (2011) presented evidence for an initial ratio of 60 Fe/ 56 Fe less than 3 × 10 −9 , roughly 100 times smaller than previously published ratios (e.g., Mishra et al 2010), while Tang & Dauphas (2012) found an initial ratio of 1 × 10 −8 . The initial level of 60 Fe is particularly significant, as its efficient production requires stellar nucleosynthesis (Tachibana et al 2006) in either a massive star supernova or an AGB star (Huss et al 2009).…”
Section: Introductioncontrasting
confidence: 47%
“…Assuming the suitability of our shock front parameters, the 3D models show that a relatively small number of RT fingers are likely to have been involved in the injection of the SNR SLRIs into the solar nebula, which has significant consequences for the processes of mixing and transport that occurred after injection into the nebula (e.g., Boss 2011) and for the resulting levels of isotopic homogeneity and heterogeneity (e.g., Bouvier & Wadhwa 2010;Schiller et al 2010;Larsen et al 2011;Makide et al 2011;Wang et al 2011;Boss 2012). Furthermore, our estimates of injection efficiencies and dilution factors will become important discriminators for judging the likelihood of the supernova triggering and injection scenario once a clearer picture emerges of the initial abundances of the SLRIs (principally 60 Fe: Moynier et al 2011;Telus et al 2012) that were present during the formation of the various components of the most primitive meteorites.…”
Section: Discussionmentioning
confidence: 99%
“…A first generation cluster with N 1 = 5000 stars and γ SN = 0.02 is a possible reasonable solution. If, as recently suggested (Moynier et al 2011), the solar system initial abundance of 60 Fe was lower than the one usually accepted, γ SN or N 1 could accordingly be decreased.…”
Section: Constraining Generation #1: the Grandparent Cluster Sizementioning
confidence: 83%
“…As in any family, the further back in time one goes, the more difficult it is to retrieve precise information on ancestors. More knowledge will be gained on N 1 when analysts have converged on the initial solar system value of 60 Fe (Quitté et al 2010;Moynier et al 2011), along with the development of numerical simulations that will help to better constrain the value of γ SN .…”
Section: Discussionmentioning
confidence: 99%
“…Telus et al (2012) and Ogliore et al (2011), however, demonstrated that these high ratios were due to improper data reduction. Using another instrumental approach based on the analysis of bulk chondrites and differentiated meteorites, a diversity of groups have suggested that the initial solar system 60 Fe/ 56 Fe ratio was two orders of magnitude lower than previously thought, with an upper limit of 1 × 10 −8 (Tang & Dauphas 2012;Moynier et al 2011;Quitté et al 2011). Very few chondrules still show higher initial ratios (Mishra & Chaussidon 2014), possibly because of nickel redistribution on the mineral scale (Chaussidon & Barrat 2009) 60 Fe has been positively detected in very few objects, if any, this short-lived radionuclide seems to have been homogeneously distributed in the SPD (Tang & Dauphas 2012).…”
Section: Experimental Datamentioning
confidence: 98%